Efektivitas Tempat Sampah Dua Sekat terhadap Pemahaman Pemilahan Sampah di SDN 173632 - Kevin Ardin Hulu; Febertin Gulo; Dionisius Sianipar; Gabriel Lumban Tobing; Indra Sihombing (Jurnal Kemitraan Masyarakat, 2025)
Waste sorting is one of the important steps in sustainable environmental management. However, elementary school students' awareness in sorting organic and non-organic waste is still relatively low. This can have an impact on increasing the volume of waste that is not managed properly, which ultimately contributes to environmental pollution. This community service aims to measure the effectiveness of the use of two-compartment trash bins in improving students' understanding of waste sorting. The method used is observation with an action study approach on elementary school students. The results of observations after socialization showed an increase in students' understanding after the use of two-compartment trash bins, which was reflected in the increased accuracy in disposing of waste into the appropriate compartment. The use of two-compartment trash bins has proven effective in increasing students' awareness and habits in sorting waste.